2023
DOI: 10.1039/d3fo00085k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cooking methods of red-skinned onion on metabolic transformation of phenolic compounds and gut microbiota changes

Abstract: The recipient work investigated on the stability and bioaccessibility of phenolics of red-skinned onion (RSO) differently cooked and in turn on its impact on the gut microbiota and phenolics metabolism....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Colon metabolism of glycosylated quercetin derivatives begins with the hydrolysis of the glucoside moiety, releasing the corresponding aglycone that undergoes C-ring fission generating the transient intermediate 3-(3 ,4 -dihydroxyphenyl)propanoic acid that is further dehydroxylated to 3-(3 -hydroxyphenyl)propanoic acid or oxidated to 3-(3 ,4dihydroxyphenyl)acetic acid. These last compounds may finally be converted into 3-(3hydroxyphenyl)acetic acid by oxidation and dehydroxylation, respectively (Figure 4) [27,28,39]. Similarly, the colon metabolism of chlorogenic acids starts with the hydrolysis of the ester bond between quinic acid and hydroxycinnamic acid, producing 3 ,4 -dihydroxycinnamic acid which is further reduced and dehydroxylated to 3-(3 -hydroxyphenyl)propanoic acid (Figure 4) [27,30].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Colon metabolism of glycosylated quercetin derivatives begins with the hydrolysis of the glucoside moiety, releasing the corresponding aglycone that undergoes C-ring fission generating the transient intermediate 3-(3 ,4 -dihydroxyphenyl)propanoic acid that is further dehydroxylated to 3-(3 -hydroxyphenyl)propanoic acid or oxidated to 3-(3 ,4dihydroxyphenyl)acetic acid. These last compounds may finally be converted into 3-(3hydroxyphenyl)acetic acid by oxidation and dehydroxylation, respectively (Figure 4) [27,28,39]. Similarly, the colon metabolism of chlorogenic acids starts with the hydrolysis of the ester bond between quinic acid and hydroxycinnamic acid, producing 3 ,4 -dihydroxycinnamic acid which is further reduced and dehydroxylated to 3-(3 -hydroxyphenyl)propanoic acid (Figure 4) [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the colon metabolism of chlorogenic acids starts with the hydrolysis of the ester bond between quinic acid and hydroxycinnamic acid, producing 3 ,4 -dihydroxycinnamic acid which is further reduced and dehydroxylated to 3-(3 -hydroxyphenyl)propanoic acid (Figure 4) [27,30]. Thus, the most important metabolites identified after colon fermentation of glycosylated quercetin derivatives are quercetin aglycone, 3-(3 ,4 -dihydroxyphenyl)acetic acid, 3-(3 -hydroxyphenyl)acetic acid and 3-(3hydroxyphenyl)propanoic acid, whereas colon metabolism of chlorogenic acids mainly results in the accumulation of 3-(3 -hydroxyphenyl)propanoic acid [27,28,30,39,40]. In this study, we found that both parent compounds (i.e., glycosylated quercetin derivatives, quercetin aglycone and chlorogenic acids) as well as their most important colon metabolites were able to inhibit colon cancer cell proliferation at a concentration of 100 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations